Occlusal caries diagnosis and treatment - Maristela Maia Lobo; Giovana Daniela Pecharki; Lívia Litsue Gush; Débora Dias Silva; Silvia Cypriano; Marcelo de Castro Meneghim; Antonio Carlos Pereira (Universidade Estadual de Campinas, 2015)
The occlusal surface has been considered the most suitable site for carious attack for its complex anatomy and posterior location. These characteristics facilitate plaque accumulation and difficult clinical perception of visual changes on pits and fissures. Complementary diagnostic methods have been developed in order to achieve early and individualized diagnosis, as well as to monitor carious lesions progression. The viability of these methods in clinical practice and their capacity in predicting activity and severity of caries are decisive factors in treatment planning. This literature review aims to gather information about the controversial issue of occlusal caries diagnosis and its treatment.